The Urgency of Strengthening Civic Education in Shaping Social Ethics in The Digital Era - Wati, Ikmah; Wati, Irna; Muharom, Syahrul; Gunawan, Muhamad Ihsan (The Future of Education Journal, 2026)
Civics Education plays a crucial role in instilling social values in the younger generation. In today's digital age, the decline of social ethics among the younger generation is a serious problem. Social ethics, as the foundation of social life for harmony, must be mastered by every individual. This study aims to examine the strengthening of Civics Education in shaping social ethics for students in the digital age. This research uses qualitative methods that refer to literature studies. The data from this study refer to various relevant scientific journals. The results indicate that humanistic values need to be focused on Civics Education, that they require an understanding of the challenges in instilling social values, and that an appropriate strengthening strategy is required in Civics Education. The recommendations in this study are the need for evaluation and effective collaboration between various parties, including the government, society, the younger generation, institutions, stakeholders, and others, to strengthen the Civics Education system in shaping social ethics in the digital age.